Role of Effective Planning Process in Boosting Dry Port Efficiency: A Case study of Central Pakistan - Jamshaid Alam (International Journal of Supply Chain Management, 2016)
Inland Dry Port terminal has become a very effective tool of enhancement of port capacity through its vertical integration with the hinterland and it results in tremendous direct and indirect benefits as envisaged in the literature. These benefits cannot be achieved without identifying and involving the proper stakeholders in the planning process and operations. Multan Dry Port was established in 1995 and it is marked by inefficiency and could not attract the customers and failed to achieve the benefits of its establishment. This paper identifies the bottlenecks and the flaws in the planning process which contributed towards the inefficiency of the port. In Pakistan, there are many dry ports working to facilitate the imports and exports. Multan being central place of the biggest province of Pakistan is playing crucial role in uplift of national economy. In this regard Multan Dry Port facility is an important hallmark. This research is a real attempt by which problems faced by Dry Port located in central Pakistan e.g Multan Dry Port, are identified. Connectivity of the dry port with seaport through rail link is a fundamental characteristic and it is missing in case of Multan Dry Port. Due to absence of the rail link it cannot get benefit of economies of scale and the cost of bonded carrier make the consignment uneconomical. The paper analyses the intermodal potential and proposes an intermodal node over the existing railways network facilitating Multan Dry Port operations. The paper also devises a theoretical framework for the planning process of the dry ports in future identifying the actors and their role in boosting dry port efficiency.